Post-traumatic stress symptoms in hemodialysis patients with MERS-CoV exposure - Cho, A Jin; Lee, Hong-Seock; Lee, Young-Ki; Jeon, Hee Jung; Park, Hayne Cho; Jeong, Da-Wun; Kim, Yang-Gyun; Lee, Sang-Ho; Lee, Chang-Hee; Yoo, Kyung Don; Wong, Ae Kyeong (BioPsychoSocial medicine, 2020)
Background Post-traumatic stress symptoms can occur in patients with medical illness. During the Middle East Respiratory Syndrome (MERS) outbreak in South Korea in 2015, some dialysis patients in three centers who were incidentally exposed to patients or medical staff with confirmed MERS-CoV infection were isolated to interrupt the spread of the infection. We aimed to investigate post-traumatic stress symptoms and risk factors among these patients. Materials and methods In total, 116 hemodialysis (HD) patients in contact with MERS-CoV-confirmed subjects were isolated using three strategies, namely, single room isolation, cohort isolation, and self-quarantine. We used the Impact of Event Scale-Revised-Korean (IES-R-K) to examine post-traumatic stress symptoms at 12 months after the isolation period. Results Of the 116 HD patients, 27 were lost to follow-up. Of the 89 patients, 67 (75.3%) completed the questionnaires. Single room isolation was used on 40 (58.8%) of the patients, cohort isolation on 20 (29.4%), and self-imposed quarantine on 8 (11.8%). In total, 17.9% of participants ( n = 12) reported post-traumatic stress symptoms exceeding the IES-R-K’s cutoff point (≧18). Prevalence rates of IES-R-K ≧18 did not differ significantly according to isolation method. However, isolation duration was linearly associated with the IES-R-K score (standardized β coefficient − 0.272, P = 0.026). Scores in Avoidance, Emotional numbing and Dissociation subscale were higher in patients with longer isolation period. Conclusion MERS was a traumatic experience for quarantined HD patients. IES-R-K scores were not significantly different by isolation methods. However, short isolation was associated with post-traumatic stress symptoms.